Balance and digestibility of nitrogen, when using distiller?s vinasse as partial substitute of the protein source in growing-fattening swine - Alberto, Mayren; Sav?n, Lourdes; Mart?nez, Olga; Mora, Luis M.; Mac?as, M. (Cuban Journal of Agricultural Science, 2011)
Six Yorkshire-Landrace x Duroc barrows with average weight of 35 kg were used in a 3 x 3 Latin square design. The objective was to determine the balance and the digestibility of nitrogen in conventional corn-soybean diets, substituting 0, 15, and 30 % of the soybean protein by distiller?s vinasse. The animals were allocated in metabolism cages with equal conditions. Dry matter and nitrogen digestibility, nitrogen balance, and retention of the digested and consumed material in g/d were determined. The results evidenced a positive balance. There were differences (P < 0.05) in dry matter digestibility for the different levels (0, 15, and 30 %) (84.16, 84.42, and 87.85%). In the control treatment, the urinary excretion of N in g/d differed (P < 0.05) compared to the rest, retaining larger amount of nitrogen in the treatments with vinasse (7.47, 4.48, and 5.01). It is concluded that it is likeable the inclusion of distiller?s vinasse, up to 30 %, in growing pig diets, not affecting the physiological and metabolic performance. Key words: vinasse, pigs, nitrogen balance, digestibility.